Minos’ silver Wine-Cup : religious forgery, reception and functional memory in classical antiquity - Gordon, Richard (ARYS. Antigüedad: Religiones y Sociedades, 2020)
Modern interest in forgery takes many forms. Popular interest is mostly in scandal, and implicitly the maintenance of a Romantic myth of authenticity; connoisseurship is concerned with the preservation and enhancement of commercial value; academic interest is directed towards the possibilities opened up by the ‘death of the author’. In the field of Classics, it is forgers’ intentions that have traditionally been the focus of attention. Adopting a communication-model, this article considers religious forgery from the point of view of reception, the interests at work in the process of acceptance and (occasional) rejection. Forgeries are understood as aspirant contributions to cultural memory, so that it becomes necessary to consider degrees of consensual legitimacy, and operative concepts of plausibility.